2018
DOI: 10.1007/s12178-018-9515-y
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Plasma: Review of Current Literature on its Use for Tendon and Ligament Pathology

Abstract: Recent literature has shown moderate- to high-quality evidence that PRP can have positive clinical effects in certain conditions such as lateral epicondylitis and rotator cuff tendinopathy. Prospective studies have shown that it can also be useful in the treatment of patella tendinopathy. In summary, we found PRP to have variable success in ligament and tendon pathology; however, it should be considered a viable option in chronic musculoskeletal disease that has failed other treatments. Patient selection, dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 67 publications
1
54
0
2
Order By: Relevance
“…Injection of PRP in these patients may have reduced the carpal tunnel tendon and MN inflammation present in this cohort, thus benefitting, not only the muscles innervated by the distal branches of the MN, but all the irrigated flexor tendons within the carpal tunnel which are the primarily responsible for transferring tensile loads to hand grip (digitorum profundus and superficialis tendons). In this sense, several in vitro and in vivo studies have shown that PRP has anti-inflammatory effects and improves tendon healing, and have elucidated its molecular mechanism of action in this context [51][52][53][54][55][56][57][58][59][60][61] . Nonetheless, other human studies reported that PRP had no beneficial effects on tendon healing [62][63][64][65][66] , or only found them after longer follow-ups [67][68][69][70] .…”
Section: Discussionmentioning
confidence: 99%
“…Injection of PRP in these patients may have reduced the carpal tunnel tendon and MN inflammation present in this cohort, thus benefitting, not only the muscles innervated by the distal branches of the MN, but all the irrigated flexor tendons within the carpal tunnel which are the primarily responsible for transferring tensile loads to hand grip (digitorum profundus and superficialis tendons). In this sense, several in vitro and in vivo studies have shown that PRP has anti-inflammatory effects and improves tendon healing, and have elucidated its molecular mechanism of action in this context [51][52][53][54][55][56][57][58][59][60][61] . Nonetheless, other human studies reported that PRP had no beneficial effects on tendon healing [62][63][64][65][66] , or only found them after longer follow-ups [67][68][69][70] .…”
Section: Discussionmentioning
confidence: 99%
“…Etiology may direct choose the type of PRP, for instance leukocyte-rich versus leukocyte-poor. Acellular pathologies such as lateral epicondylitis may benefit from leukocyte-rich PRP, which may help induce an inflammatory response to stimulate healing (6) . Magalon and colleagues (38) retrospectively applied their proposed classification (DEPA: Dose of injected platelets, Efficiency of production, Purity of the PRP, Activation of the PRP) on twenty PRP preparations -for which biological characteristics were available in the literature-to characterize the injected PRP.…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Platelets are natural source of various growth factors. Upon activation, platelets release the stored intercellular mediators and cytokines from the cytoplasmic pool Table 1: Functions of the growth factors and cytokines in the platelet rich plasma (1,(6)(7)(8)(9) .…”
Section: Functionmentioning
confidence: 99%
“…Walters et al recently conducted a randomized control trial on the use of PRP to augment patellar tendon autograft ACL reconstruction with minimal success. While the lack of high‐level clinical evidence remains a concern, PRP remains a viable conservative treatment with a low risk of complications or adverse reactions . The primary drawback for clinical use is the out‐of‐pocket costs to patients, as insurance seldom covers the cost of PRP treatment.…”
Section: Therapeutic Approaches To Augment Healing In Tendon and Ligamentioning
confidence: 99%